Chile : 2013 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2013)
The staff reports for the 2013 Article IV Consultation on the Chile discuss the strong and inclusive growth over the medium term. Technocratic, rules-based, and transparent policy management; monetary policy under a floating exchange rate undertaken by a credible central bank; and prudent fiscal policy, since 2001 under a near-legendary fiscal rule, has enhanced policy clarity, reinforced Chile's resilience to shocks, and allowed for vigorous policy responses when needed, as after the global financial crisis and the earthquake. The widening current account deficit and the increased reliance on debt financing have increased balance of payments stability risks and Chile's exposure to sudden stops.